A new species of Oreobates (Anura: Strabomantidae) from the Andes of northern Argentina - Vaira, Marcos; Ferrari, Liliana (Zootaxa, 2008)
Oreobates barituensis sp. nov. is described from the ecoregion of southern Andean Yungas forests of north-western Argentina at elevations of 1100 to 1300 m above see level. It shares morphological characters with the sympatric and syntopic O. discoidalis, as well as with O. ibischi and O. cruralis from Bolivia. The recognition of the new species is in particular supported by considerable differences in the advertisement call among these species. We also made some considerations on probable conspecificity of northern Argentina and Bolivian populations of O. discoidalis and O. cf. cruralis.